(untitled) (Research, Society and Development, 2022)
Analyze whether there are suicidal ideations, identify what the motivations are, and describe the sociodemographic and economic profile of university students. Quantitative, cross-sectional study with undergraduate students from the State University of Minas Gerais – UEMG – Divinópolis in 2020. A Sociodemographic Questionnaire, Suicide Ideation Questionnare (QIS), Beck Scale and Satisfaction with Social Support Scale (ESSS) were used. The chi-square test, Fisher’s exact test, calculation of the Odds-Ratio (OR) was performed. Both statistical tests were performed using the Statistical Package for Social Sciences (SPSS) program. 130 university students participated in the study, predominantly female (81.5%), aged between 21 and 25 years (61.5%) and single (78.5%). Of the total sample, 28 (21.53%) were at risk of having suicidal ideation. It was listed that students who live in another city are 1.52 times more likely to have suicidal ideation (CI=0.65-3.55), who have a monthly income less than or equal to the minimum wage increases by 2 times the chances of having suicidal ideation (CI: 0.74-0.53) and claiming to suffer from some mental or behavioral disorder increases by 1.40 times the chances of suicidal ideation (CI=0.60 to 3.25). Knowing the mental characteristics of university students makes it possible to plan joint interventions in the academic community and develop prevention and promotion strategies, reducing suicidal ideation in this public.